OCEAN ISLAND DENSITIES AND MODELS OF LITHOSPHERIC FLEXURE - Minshull T.A.; Charvis Ph. (My University, 2001)
Estimates of the effective elastic thickness (Te) of the oceanic lithosphere based on gravity and bathymetric data from island loads are commonly significantly lower than those based on the wavelength of plate bending at subduction zones. The anomalously low values for ocean islands have been attributed to the finite yield strength of the lithosphere, to erosion of the mechanical boundary layer by mantle plumes, to pre-existing thermal stresses and to overprinting of old volcanic loads by younger ones. A fifth possible contribution to the discrepancy is an incorrect assumption about the density of volcanic loads. We suggest that load densities have been systematically overestimated in studies of lithospheric flexure, potentially resulting in systematic underestimation of effective elastic thickness and overestimation of the effects of hotspot volcanism. We illustrate the effect of underestimating load density with synthetic examples and an example from the Marquesas Islands. This effect, combined with the other effects listed above, in many cases may obviate the need to invoke hotspot reheating to explain low apparent elastic thickness.
Keywords: DENSITY; GRAVITY ANOMALIES; LITHOSPHERIC FLEXURE; OCEAN ISLANDS; RHEOLOGY; VOLCANIC STRUCTURE